Development of Texture in Interstitial-Free Steel Processed by Equal-Channel Angular Pressing - Verma D.; Shekhawat S.K.; Mukhopadhyay N.K.; Sastry G.V.S.; Manna R. (My University, 2025)
Ti + Nb-stabilised interstitial-free steel is deformed by equal-channel angular pressing (ECAP) adopting a route BC up to an equivalent strain of 24. Upon ECAP the grain size decreases to ultrafine level and it becomes strongly textured. At εvm = 0.6-6, components of both {110} fiber, (Formula presented.) , (Formula presented.) and of 〈111〉 fiber, D1θ,D2θ with common components of Eθ, (Formula presented.) are existing but after εvm ≥9, only 〈111〉 fiber components are observed. At large strain, εvm = 9-24, 〈111〉 fiber texture is recorded with monoclinic symmetry. At εvm = 0.6, coarse grains get split into deformation bands. Fragmentation of bands (at εvm = 3) suppress (Formula presented.) (Formula presented.) components. At εvm = 6, formation of lamellar structures increases intensity of mainly D1θ,D2θ. At εvm = 9, oriented ribbon grains result in strong D1θ,D2θ components with 〈111〉 fiber. At εvm = 15-24, conversion of ribbon grains to near-equiaxed shaped grains maintains 〈111〉 fiber texture with enhanced intensity of D1θ and D2θ components. © 2016, ASM International.